The Use and Effect of the Health Storylines mHealth App on Female Childhood Cancer Survivors' Self-efficacy, Health-Related Quality of Life and Perceived Illness. Issue 1 (18th January 2022) - Cantrell, Mary Ann; Ruble, Kathy; Mensinger, Janell; Birkhoff, Susan; Morris, Amanda; Griffith, Patricia; Adams, Jared
Abstract : Background: mHealth apps have been not been well tested among childhood cancer survivors (CCSs) to track physical and psychosocial functioning for improved self-management of post-treatment needs. Objectives: This pilot study had 3 aims: (1) assess the usage of the Health Storylines mHealth app; (2) examine its effect in improving self-efficacy in managing survivorship healthcare needs, health-related quality of life, and perceived illness; and (3) determine if app usage moderated the effects on the above patient-reported outcome measures among female CCSs. Methods: Study participants accessed the Health Storylines mHealth app on their own personal device. This single-group, pilot study included 3 measurement points: baseline and 3 and 6 months after initiation of using the app. Results: Use of the mHealth app ranged from 0 times to 902 times. Every study participant who used the app (n = 26) also used the mental health app component of the Health Storylines app. Generalized estimating equations were fit to examine the effect of the mHealth app use on self-efficacy, perceived illness, and health-related quality of life, between baseline, 3-month follow-up, and 6-month follow-up. No statistically significant changes were evident, on average, from baseline to 3- or 6-month follow-up on any outcome. Subsequent testing of effect moderation showed differential trends for high versus low users. Conclusions: Studies are needed among this clinical population to determine who will benefit and who will perceive the app as a useful aspect of their survivorship care. Implications for Practice: Sharing mental health functioning tracked on mhealth apps with healthcare providers may inform needed interventions for young adult female CCSs.